Study of Transaminases in Heroin Addicts - Rino A Gani; Agus Sudiro Waspodo; Unggul Budihusodo; Irsan Hasan; Muhammad Sjaifoellah Noer (The Indonesian Society for Digestive Endoscopy, 2001)
A recent increase in the number of drug users particularly of heroin has been noted in the community. A cross-sectional study on the level of transaminases as a representation of liver damage in drug users was done in privated hospital in Jakarta. Exclusion criteria were fever, serious illness or the multiple use of addictive drugs based on a urinary test. The hepatitis B surface antigen (HBsAg) was examined using reverse passive hemaglutination assay (RPHA) and the antibody of hepatitis C virus core-protein (anti- HCV) with dipstick anti-HCV. AST and ALT levels were determined using an automatic chemical analyzer. Of 132 patients who fulfill the criteria, 83.5 % were injection drug users (IDU). Means AST and ALT were significantly higher in IDU. Anti-HCV positive patients with increased AST and ALT were significantly higher compared to anti-HCV negative. The increase of transaminase was also consistent in injection drug users although no viral marker could be detected. In conclusion, the examination of transaminases in drug users especially IDU is important besides tests for hepatitis viral markers because there is often an increase with or without viral infection and this can be associated with hepatocellular damage. Key words: Transaminase, heroin addicts, hepatitis